Hubungan Problem Focused Coping dengan Workload pada Pegawai Minimarket di Kabupaten Bekasi - Yogi Febriyanto; Andreas Corsini Widya Nugraha; Arfian A (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Workload is one of the major challenges faced by employees in the retail sector, particularly minimarket employees who are required to perform multiple tasks simultaneously under demanding working conditions. Effective coping strategies are therefore essential to help employees manage these work demands. This study aimed to examine the relationship between problem-focused coping and workload among minimarket employees in Bekasi Regency. A quantitative correlational research design was employed involving 100 minimarket employees selected using quota sampling. Data were collected using the Problem-Focused Coping Scale based on Carver et al. (1989) and the NASA Task Load Index (NASA-TLX) developed by Hart and Staveland (1988). Pearson Product-Moment correlation analysis was performed using JASP software. The findings revealed a significant positive relationship between problem-focused coping and workload (r = 0.782; p 0.001). The results indicate that employees experiencing higher workloads tend to employ problem-focused coping strategies more frequently. Most respondents demonstrated high levels of problem-focused coping, while their perceived workload was at a moderate level. These findings suggest that problem-focused coping functions as an adaptive strategy enabling employees to manage increasing work demands rather than directly reducing workload. The study contributes to the understanding of coping mechanisms among retail employees and provides practical implications for organizational efforts to strengthen employees' adaptive coping strategies.